Pendampingan Penyusunan Aplikasi Laporan Keuangan Badan Keswadayaan Masyarakat (BKM) - Hanifah, Risti Ulfi; Yulianti, Yulianti; Iqbal, Mohamad (Universitas Negeri Semarang, 2021)
BKM is a citizen institution whose emergence in the community is intended as a community organization that favors helping the needs of the community, especially those related to poverty. A BKM policy is carried out technically by the Managing Unit. UPK as a Financial Management Unit in charge of distributing finance to KSM through BKM decisions. The potential of BKM, while currently still struggling with economic issues. In BKM, Dadi Mulya financial management unit gets some constraints that slow down performance. The main problems that exist occur in the accounting process in the preparation of financial statements and human resource management.Thus, the service team provides solutions or problem solving that is helping and accompanying BKM Dadi Mulya or UPK in presenting financial statements based on transaction documents or other related documents so that they become complete and complete financial statements in accordance with generally grateful financial accounting standards. As well as assisting using the application so as not to use manual recording to facilitate in the creation of financial statements. The participants who participated in this activity understood the management of application-based BKM financial statements well. After the completion of the event, interviews were conducted to all participants to evaluate the activities carried out by the service team. The results showed that most of the participants stated that they understood the material delivered by the speaker.